Crystal defect-mediated band-gap engineering: a new strategy for tuning the optical properties of Ag2Se quantum dots toward enhanced hydrogen evolution performance1. Issue 40 (28th October 2015) - Cao, Qi; Cheng, Yi-Feng; Bi, Han; Zhao, Xuebing; Yuan, Kaiping; Liu, Qinghe; Li, Qingqing; Wang, Min; Che, Renchao
<x xml:space="preserve">Abstract</x> Defect-rich Ag2Se QDs were prepared controllably for sensitizing TiO2 toward high-performance visible-light-driven hydrogen-evolution photocatalysts.